A post-punching shear model for column–slab connections for progressive collapse analyses. Issue 6 (1st March 2022) - Ulaeto, Nsikak W.; Sagaseta, Juan
Abstract : Progressive collapse of concrete flat slab structures is mainly governed by the structural response of the slab–column connections before and after local failure of the connections. A novel model is proposed to predict the structural response of column–slab connections after punching shear failure (post-punching shear). The proposed model considers the gradual activation and deactivation of flexural bars within and outside the punching shear cone as well as the contribution of integrity reinforcement. The model is formulated in terms of slab vertical displacements so that it can be applied to progressive collapse analyses including asymmetric cases such as in column removal scenarios commonly adopted in structural robustness design. The proposed model is validated using existing experimental data covering symmetric post-punching tests without shear reinforcement, with and without integrity reinforcement. Numerical modelling was also applied to verify the analytical model by means of three-dimensional explicit finite element modelling. Analytical and numerical models showed that asymmetric post-punching leads to a reduction of the peak post-punching strength due to an early fracture of the reinforcement whereas the residual shear strength in the connection immediately after punching can be higher in asymmetric cases.